STUDI PERBANDINGAN ANTARA AMR DALAM ILMU BALAGHAH DAN ILMU USHUL FIQH SERTA APLIKASINYA TERHADAP PEMBELAJARAN - Rizki Abdurahman, - (2012)
diantaranyaadalahilmuBalaghahdanilmuUshulFiqih.IlmuBalaghahmerupakansalahsatudisiplinilmu yang berkaitandenganmasalahkalimat, yaitumengenaimaknanya, susunannya, pengaruhjiwaterhadapnya, sertakeindahandankejelianpemilihan kata yang sesuaidengantuntutan.SedangkanilmuUshulFiqihadalahkaidah-kaidah yang dipergunakanuntukmengeluarkanhukumdaridalil-dalilnya, dandalil-dalilhukum (kaidah-kaidah yang menetapkandalil-dalilhukum).SebagaimanakitaketahuibahwaobjekkajianilmuBalaghahdanUshulFiqhitumemilikiperbedaan yang sangatmenonjol.DalamilmuBalaghahdibahastentangilmuMa'ani,ilmuBayan danilmuBadi'.SedangkanobjekpembahasandalamUshulFiqihyaitudalilsyara' yang bersifatumumditinjaudariketepatannyaterhadaphukumsyara' yang umum pula.Tetapi, walaupundemikianternyatasetelahpenelitimengamatiobjekkajiankeduanya, diantaranyaadaobjekkajian yang sama, yaitutentangAmratau kata perintah. PermasalahannyaadalahapakahAmrdalamBalaghahdanUshulFiqihiniberbedaatausama. TujuandaripenelitianiniadalahuntukmengetahuiaspekpersamaandanperbedaanAmr yang adadalamBalaghahdanUshulFiqhsertaaplikasinyaterhadappembelajarankeduanya.Adapunmetodepenelitianyang digunakanadalahstudiperbandingandenganpendekatankualitatif.PopulasidalampenelitianiniadalahAmr, sedangkansampelnyaadalahAmr yang terdapatdalamBalaghahdanUshulFiqh.Pengumpulan data yang digunakanolehpenulisyaitustudidokumentasi, sedangkanlandasanteoretikdalampenelitianiniadalahpembahasanseputarAmrmenurutBalaghahdanUshulFiqih.HasiltemuannyaadalahadanyaaspekpersamaandanperbedaanantaraAmrdalamBalaghahdanUshulFiqih.Persamaannyameliputiaspekdefinisi, sebagianshigohdansebagianmaknanya. Ada limashigoh yang samaantaraAmrdalamBalaghahdanUshulFiqih, danada 22 makna yang samaantaraAmrdalamBalaghahdanUshulFiqh. Sedangkanaspekperbedaanyameliputisebagianshigoh, sebagianmaknadankaidah-kaidahAmr.Ada 11 shighohAmr yang hanyaadadalamUshulFiqih, dantidakadadalamBalaghah.Ada satushighohAmr yang hanyaadadalamBalaghahdantidakadadalamUshulFiqih. Ada empatmakna yang khususdalamBalaghahdantidakadadalamUshulFiqih, sertaada 10 makna yang khususdalamUshulFiqihdantidakadadalamBalaghah. SedangkanuntukkaidahAmr yang dapatmengistinbathhukumhanyaadadalamUshulFiqhdenganjumlah 18 kaidah.Rekomendasidaripenelitianiniadalahhendaknyaparadosen, siswasertapecintailmuBalaghahdanUshulFiqihdapatmengaplikasikankajianinidenganterusmenerusmencermatiAmr yang terdapatdalamAlqurandanhaditsdengancaramenyorotiaspekpersamaandanperbedaannyamenuruttinjaunBalaghahdanUshulFiqih. Penelitiberharapsemogahasilpenelitianinibisamemberikankontribusi yang signifikanbagipengembangankajianimuBalaghahdanilmuUshulFiqih.Wallahu 'Alam bi Showab. ABSTRACT Qur'an and the hadith are the main sources of Islamic law. Required to disclose its contents contains various disciplines of science facilities, including the science and the science of UsulFiqhBalaghah. Balaghah science is one discipline that deals with the problem sentence, which is about the meaning, structure, influence of soul to it, as well as the beauty and smartness of the word according to the demands. While knowledge is UsulFiqh rules are used to remove the law from their arguments, and arguments of law (the rules that define the legal arguments). As we know that the object of scientific study and UsulFiqhBalaghah it has a very prominent. In a discussion about the science of science BalaghahMa'ani, science and science Bayan Badi '. While the object of discussion in UsulFiqh is the argument of Personality 'a general review of its accuracy against the law Personality' are also common. But, however it turns out after the second study researchers looked at the object, the object of which there are similar studies, that of Amr or word order. The issue is whether Amr in UsulFiqhBalaghah and this is different or the same. The purpose of this study is to investigate aspects of the similarities and differences that exist in BalaghahAmr and UsulFiqh and its application to learning both. The method of study is a comparative study with a qualitative approach. The population in this study is Amr, Amr while the sample is contained in and UsulFiqhBalaghah. The collection of data used by the authors study the documentation, while the theoretical foundation in this study is the discussion around Amr and UsulFiqh according Balaghah. Aspects of its findings is the existence of similarities and differences between Amr and UsulFiqh in Balaghah. The equation includes the aspects of the definition, some shigoh and some meaning. There are five similar shigoh between Amr and UsulFiqh in Balaghah, and there are 22 similar meaning between Amr and UsulFiqh in Balaghah. While covering most aspects of the difference shigoh, some meaning and the rules of Amr. There are 11 shighohAmr that exists only in UsulFiqh, and not in Balaghah. There is only one Amrshighoh in Balaghah and not in the UsulFiqh. There are four special meaning in Balaghah and not in the UsulFiqh, and there are 10 special meaning in UsulFiqh and not in Balaghah. As for the rule of law mengistinbathAmr that can only exist in UsulFiqh by the number of 18 rules. Recommendations from this study is should the faculty, students and lovers of science and UsulFiqhBalaghah can apply this study to continuously watch Amr contained in the Qur'an and the Hadith by way of highlighting aspects of the similarities and differences in UsulFiqh and tinjaunBalaghah. Researchers hope that this research could make a significant contribution to the development review of astronomy and science of UsulFiqhBalaghah. Allaah 'Alam bi Showab.